A method for preparing zinc selenide

CN122685023APending Publication Date: 2026-09-04ZIJIN MINING GROUP CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611044450.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-09-04

AI Technical Summary

Technical Problem

目前实际应用中,硒化锌材料仍以单一立方相(闪锌矿结构)为主,其稳定性、光学均匀性及力学性能更契合工业生产与器件制备的需求,而六方相(纤锌矿结构)作为高温相,会显著影响产品性能,限制其实际应用范围

Benefits of technology

(1)本发明采用复合无机盐粉末具有以下的特点:1)利用复合无机盐粉末的吸热效应,控制自蔓延合成法制备立方硒化锌过程的温度,实现了立方相硒化锌粉体制备过程的可控;2)利用复合无机盐粉末的水溶性,产物通过简单的酸洗即可实现提纯。因此,本发明能够实现立方相硒化锌单相材料的低成本、高效率制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122685023A_ABST
    Figure CN122685023A_ABST
Patent Text Reader

Abstract

The application provides a preparation method of zinc selenide and relates to the technical field of semiconductor materials. In the self-propagating reaction of zinc powder and selenium powder, composite inorganic salt powder is added as a diluent and a reaction temperature regulator, so that the reaction temperature can be well controlled, the reaction speed is high, the reaction uniformity is good, and zinc selenide with high purity and single-phase cubic crystal can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of semiconductor materials technology and relates to a method for preparing zinc selenide. Background Technology

[0002] Zinc selenide (ZnSe), as an important group II-VI wide-bandgap semiconductor compound, possesses excellent optical, electrical, and thermal properties, playing an irreplaceable key role in fields such as infrared optics, laser technology, and optoelectronic devices. Currently, in practical applications, zinc selenide materials are still predominantly in a single cubic phase (zinc sphalerite structure), whose stability, optical homogeneity, and mechanical properties better meet the needs of industrial production and device fabrication. In contrast, the hexagonal phase (wurtzite structure), as a high-temperature phase, significantly affects product performance and limits its practical application range.

[0003] The self-propagating reaction method using zinc powder and selenium powder is one way to prepare zinc selenide. However, the current self-propagating reaction method still has problems such as low controllability of the reaction process, loss of selenium powder, and insufficient purity of zinc selenide. For example, the boiling point of selenium is 685℃, while the temperature of the self-propagating reaction can reach above 700℃, resulting in significant volatilization of selenium. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a method for preparing zinc selenide.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing zinc selenide includes the following steps: The reaction raw materials, consisting of zinc powder, selenium powder, and composite inorganic salt powder, are mixed evenly and then subjected to a self-propagating reaction to obtain a mixture. The composite inorganic salt powder is composed of at least two inorganic salts, and the eutectic point temperature is 475-600℃; The mixture is soaked in a weakly acidic aqueous solution to remove soluble substances, then washed with water and dried to obtain zinc selenide; The zinc selenide has a cubic phase.

[0007] Preferably, the stoichiometric ratio of the zinc powder to the selenium powder is 1.05-1.25:1; The purity of the zinc powder and the purity of the selenium powder are each not less than 99.95%.

[0008] Preferably, the composite inorganic salt powder accounts for 20-40% by weight in the reaction raw materials; The average particle size of the reaction raw materials is 5-50 μm.

[0009] Preferably, the at least two inorganic salts are water-soluble or acid-soluble at room temperature.

[0010] More preferably, the composite inorganic salt powder is selected from chloride salts and / or sulfate salts.

[0011] More preferably, the composite inorganic salt powder is selected from the following systems: NaCl-CaCl2 binary system, KCl-CaCl2 binary system, LiCl-Li2SO4 binary system, Li2SO4-NaCl binary system, NaCl-KCl-CaCl2 ternary system, Na2SO4-KCl-CaCl2 ternary system, or NaCl-KCl-BaCl2 ternary system.

[0012] In a further preferred embodiment, the weight percentage of NaCl in the NaCl-CaCl2 binary system is 40-50 wt%, and the weight percentage of CaCl2 is 50-60 wt%. The KCl-CaCl2 binary system is composed of 40-50 wt% KCl and 50-60 wt% CaCl2 by weight (100% by weight). The LiCl-Li2SO4 binary system is composed of 50-70 wt% Li2SO4 and 30-50 wt% LiCl by weight (100% by weight). The Li₂SO₄-NaCl binary system, by weight, comprises 66-78 wt% Li₂SO₄ and 22-34 wt% NaCl. The NaCl-KCl-CaCl2 ternary system, by weight, comprises 30-50 wt% NaCl, 5-20 wt% KCl, and 40-60 wt% CaCl2. The Na2SO4-KCl-CaCl2 ternary system, by weight, comprises 20-33 wt% Na2SO4, 17-25 wt% KCl, and 46-58 wt% CaCl2. The NaCl-KCl-BaCl2 ternary system is based on a 100% weight ratio, with NaCl accounting for 15-35 wt%, KCl accounting for 20-40 wt%, and BaCl2 accounting for 30-50 wt%.

[0013] Preferably, the self-propagating reaction is initiated by exothermic current in the resistance wire, with a current intensity of 3-20A and a protective gas atmosphere. The reaction temperature range of the self-propagating reaction is 475-675℃.

[0014] Preferably, the concentration of the weakly acidic aqueous solution is 0.05-0.5 mol / L; The weak acid in the weakly acidic aqueous solution is selected from organic weak acids.

[0015] More preferably, the organic weak acid is selected from one or more of malic acid, acetic acid, tartaric acid, propionic acid and citric acid.

[0016] The beneficial effects of this invention are: (1) The composite inorganic salt powder used in this invention has the following characteristics: 1) By utilizing the endothermic effect of the composite inorganic salt powder, the temperature of the self-propagating synthesis process for preparing cubic zinc selenide is controlled, thus achieving controllable preparation of cubic phase zinc selenide powder; 2) Utilizing the water solubility of the composite inorganic salt powder, the product can be purified by simple acid washing. Therefore, this invention can achieve low-cost and high-efficiency preparation of cubic phase zinc selenide single-phase materials.

[0017] (2) The eutectic point of the composite inorganic salt powder is close to the reaction temperature range of ZnSe synthesis. During the self-propagating reaction, the inorganic salt powder will completely melt and form a continuous molten salt liquid phase medium, which effectively improves the mass transfer conditions of the reaction system. At the same time, the latent heat of phase change absorbed by the composite inorganic salt powder during melting is much higher than the heat absorbed by heating alone in the same temperature range (without phase change). Therefore, the temperature control and homogenization effect of the composite inorganic salt powder on the self-propagating reaction is significantly better than that of the single salt system, and the vaporization and volatilization loss of Se can be effectively avoided.

[0018] (3) Excess Zn raw material ensures complete reaction of the more expensive elemental Se, while removing unreacted Zn and ZnO impurities by weak acid washing to obtain high-purity ZnSe product. Attached Figure Description

[0019] Figure 1 The image shows the XRD pattern of ZnSe obtained in Example 1. Detailed Implementation

[0020] The technical solution of the present invention will be further explained and described below through specific embodiments.

[0021] This invention proposes a method for preparing zinc selenide, comprising the following steps: The reaction raw materials, consisting of zinc powder, selenium powder, and composite inorganic salt powder, are mixed evenly and then subjected to a self-propagating reaction to obtain a mixture. The composite inorganic salt powder is composed of at least two inorganic salts, and the eutectic point temperature is 475-600℃. The mixture was soaked in a weakly acidic aqueous solution to remove soluble substances, then washed with water and dried to obtain zinc selenide; Zinc selenide has a cubic crystal form.

[0022] In this invention, composite inorganic salt powder is used as a diluent and temperature regulator for the reaction of zinc and selenium powders. The eutectic point temperature of the composite inorganic salt powder is 475-600℃, and it melts during the self-propagating reaction. The endothermic reaction temperature is effectively regulated through heating and melting, especially the significant heat absorption during melting. The reaction temperature for ZnSe synthesis can be controlled to remain below 600℃, far below the boiling point of Se, thus avoiding Se volatilization loss. Furthermore, the molten composite inorganic salt exhibits better mass and heat transfer than the powdered form, improving the reaction efficiency and uniformity of the self-propagating reaction. The reaction temperatures of the reactants in different parts are more similar, resulting in high-purity cubic ZnSe.

[0023] The mixture after the reaction is washed with a weakly acidic aqueous solution, which can dissolve and remove soluble substances such as complex inorganic salts, unreacted Zn powder, and ZnO, and obtain cubic ZnSe phase without reacting with ZnSe. However, if the mixture is washed with water only, it cannot effectively remove impurities such as unreacted Zn powder and ZnO, affecting the purity of the product.

[0024] There are no particular restrictions on the method for uniformly mixing the reaction materials; it can be grinding, mechanical vibration, ultrasonic vibration, etc. The container for holding the reaction materials can be a crucible, and the crucible material can be alumina, graphite, boron nitride, zirconium dioxide, etc. After the reaction materials are uniformly mixed, they can be dried to remove moisture and prevent water from being introduced into the reaction system.

[0025] In some embodiments, the stoichiometric ratio of zinc powder to selenium powder is 1.05-1.25:1; The purity of zinc powder and selenium powder shall be no less than 99.95% on their own.

[0026] When zinc powder and selenium powder react, the stoichiometric ratio is 1:1. In this invention, using a moderate excess of zinc powder can effectively promote the complete reaction of the expensive selenium powder. Excess unreacted Zn powder and the generated ZnO can be removed by washing with a weakly acidic aqueous solution. For example, the stoichiometric ratio of zinc powder to selenium powder can be 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, etc.

[0027] In some embodiments, the composite inorganic salt powder accounts for 20-40% by weight in the reaction raw materials; The average particle size of the reaction raw materials is 5-50 μm.

[0028] If the weight percentage of the composite inorganic salt powder in the reaction raw materials is too low, its effect as a diluent and reaction temperature regulator will be insufficient, making it difficult to effectively control the temperature of the self-propagating reaction within a suitable range. This may result in localized or overall excessively high temperatures in the self-propagating reaction, such as exceeding the boiling point of the selenium (Se) powder. Conversely, if the weight percentage of the composite inorganic salt powder in the reaction raw materials is too high, it will reduce the contact opportunity between the zinc (Zn) powder and the selenium (Se) powder, decreasing the reaction rate and leading to insufficient exothermic reaction, excessive endothermic reaction, and incomplete reaction between the zinc (Zn) powder and the selenium (Se) powder. For example, the weight percentage of the composite inorganic salt powder in the reaction raw materials could be 20%, 25%, 30%, 35%, or 40%.

[0029] A lower average particle size of the reactants results in higher reactivity, enabling faster reactions and better mass and heat transfer. For example, the average particle size of the reactants can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, etc.

[0030] In some embodiments, at least two inorganic salts are water-soluble or acid-soluble at room temperature. In this invention, the composite inorganic salt powder can be composed of two, three, or even more inorganic salts, all of which are water-soluble or acid-soluble at room temperature and can be completely removed by a simple acid washing operation after the reaction.

[0031] In some embodiments, the composite inorganic salt powder is selected from chlorides and / or sulfates. Chlorides and sulfates have good water solubility, dissolve quickly, and have high stability at self-propagating reaction temperatures, and will not decompose or react with Zn powder or Se powder.

[0032] Furthermore, the composite inorganic salt powder is selected from the following systems: NaCl-CaCl2 binary system (eutectic point approximately 500℃), KCl-CaCl2 binary system (eutectic point approximately 594℃), LiCl-Li2SO4 binary system (eutectic point approximately 482℃), Li2SO4-NaCl binary system (eutectic point approximately 490℃), NaCl-KCl-CaCl2 ternary system (eutectic point E1 approximately 488℃, eutectic point E2 approximately 475℃), Na2SO4-KCl-CaCl2 ternary system (eutectic point approximately 520℃), or NaCl-KCl-BaCl2 ternary system (eutectic point approximately 542℃).

[0033] Furthermore, in the NaCl-CaCl2 binary system, the weight percentage of NaCl is 40-50 wt%, and the weight percentage of CaCl2 is 50-60 wt%. In a KCl-CaCl2 binary system, the weight percentage of KCl is 40-50 wt% and the weight percentage of CaCl2 is 50-60 wt% (100% by weight). In a LiCl-Li₂SO₄ binary system, the weight percentage of Li₂SO₄ is 50-70 wt% and the weight percentage of LiCl is 30-50 wt% (by weight). In the Li₂SO₄-NaCl binary system, the weight percentage of Li₂SO₄ is 66-78 wt%, and the weight percentage of NaCl is 22-34 wt%. In a ternary system of NaCl-KCl-CaCl2, the weight percentages of NaCl are 30-50 wt%, KCl is 5-20 wt%, and CaCl2 is 40-60 wt% by weight (100% by weight). In the Na2SO4-KCl-CaCl2 ternary system, the weight percentages of Na2SO4, KCl, and CaCl2 are 20-33 wt%, 17-25 wt%, and 46-58 wt% respectively, based on a 100% weight ratio. In a ternary system of NaCl-KCl-BaCl2, the weight percentage of NaCl is 15-35 wt%, the weight percentage of KCl is 20-40 wt%, and the weight percentage of BaCl2 is 30-50 wt% by weight.

[0034] In some embodiments, the self-propagating reaction is initiated by exothermic current in the resistance wire, with a current intensity of 3-20A and a protective gas atmosphere. The reaction temperature range for the self-propagating reaction is 475-675℃.

[0035] In a self-propagating reaction, a resistance wire is inserted into the reactants, and the reaction vessel is evacuated (e.g., the vacuum pressure is as low as 10). -3 To remove moisture and humidity, a protective gas (such as argon) is added to a pressure of 0.1-2 MPa to provide an inert atmosphere. Ignition via a resistance wire current initiates a self-propagating reaction between zinc and selenium powders through exothermic reaction. The resistance wire can be tungsten, molybdenum, or nichrome wire, etc. Obviously, other methods can be used instead of resistance wire current for ignition, such as lasers, microwaves, electric sparks, and electric arcs.

[0036] In some embodiments, the concentration of the weakly acidic aqueous solution is 0.05-0.5 mol / L; The weak acid in a weakly acidic aqueous solution is selected from organic weak acids.

[0037] Using a weak organic acid can dissolve not only complex inorganic salt powders (or solid complex inorganic salts), but also excess unreacted Zn and ZnO produced by the oxidation of Zn. For example, the concentration of the weakly acidic aqueous solution can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L, 0.5 mol / L, etc.

[0038] In some embodiments, the organic weak acid is selected from one or more of malic acid, acetic acid, tartaric acid, propionic acid, and citric acid.

[0039] The technical solution of the present invention will be further described and illustrated below with reference to various embodiments. Unless otherwise specified, the parts mentioned in the following embodiments are parts by weight.

[0040] Example 1 The purity of zinc powder and selenium powder raw materials is not less than 99.95%; NaCl and CaCl2 are both reagent grade, and the content of insoluble impurities is <10ppm.

[0041] A reaction mixture consisting of 30g zinc powder (0.46mol), 29g selenium powder (0.37mol), 5.9g NaCl, and 8.85g CaCl2 (the composite inorganic salt powder composed of 5.9g NaCl and 8.85g CaCl2 has an initial melting temperature of 500℃ and a complete melting temperature of approximately 530℃) was placed in an Al2O3 crucible and mechanically vibrated for mixing. The stoichiometric ratio of Zn to Se was 1.25, the composite chloride salt accounted for 20% of the reaction mixture by weight, and the average particle size of the reaction mixture was 32μm. The Al2O3 crucible containing the mixture was placed inside a reaction vessel, and a resistance wire for initiating the reaction was inserted into the mixture. The vessel was then evacuated to 10℃. -3 Below Pa, high-purity Ar gas was refilled to 0.15 MPa. A self-propagating reaction was initiated exothermically by applying a 20 A current to a tungsten resistance wire. After the reaction was complete and the container was allowed to cool naturally, the product was opened and removed. The product was immersed in a 0.3 mol / L acetic acid aqueous solution, shaken and soaked for 5 minutes, filtered, washed three times with deionized water, and dried overnight in a vacuum oven at 60°C to obtain zinc selenide. The purity was determined to be 99.95% by inductively coupled plasma atomic emission spectrometry (ICP).

[0042] The XRD test results of zinc selenide obtained in this embodiment are attached. Figure 1 As shown in the figure, the horizontal axis represents 2θ (in degrees) and the vertical axis represents Intensity (diffraction intensity) in au. Therefore, the zinc selenide obtained in this embodiment has a single-phase cubic structure.

[0043] Comparative Example 1 The difference between this comparative example and Example 1 is that in Example 1, the combination of 5.9g NaCl and 8.85g CaCl2 was replaced with 14.75g NaCl. The remaining steps remained unchanged.

[0044] The XRD results of zinc selenide obtained in this comparative example show that the zinc selenide product contains 10.1% hexagonal zinc selenide high-temperature phase, and the remainder is cubic zinc selenide.

[0045] Therefore, NaCl was used as a diluent and temperature regulator in the above comparative example. However, NaCl has a melting point as high as 801℃, which is much higher than the boiling point of elemental Se (685℃). Therefore, NaCl remains in a solid state within the reasonable temperature range for synthesizing ZnSe (approximately 480~600℃, or slightly higher), which will hinder the mass and heat transfer of the reaction system. Furthermore, comparing the heat absorption efficiency, in Example 1, the latent heat of phase transition of the NaCl-KCl-CaCl2 ternary eutectic is approximately 178.2 J / g (melting point approximately 503.8℃), and its specific heat capacity is approximately 1.03-1.06 J / (g·℃). The specific heat capacity of NaCl is approximately 0.86 J / (g·℃). Therefore, the heat absorption required to melt 1g of NaCl-KCl-CaCl2 ternary eutectic is equivalent to the heat absorption required to raise the temperature of 1g of NaCl by approximately 207℃. Moreover, the specific heat capacity of the NaCl-KCl-CaCl2 ternary eutectic is also higher than that of NaCl. Therefore, within the reaction temperature range of 480-600℃, the heat absorption capacity of the NaCl-KCl-CaCl2 ternary eutectic is far greater than that of NaCl alone. Thus, in Example 1, after the self-propagating reaction begins, the system temperature rapidly reaches the melting point of the composite chloride salt. At this point, the composite chloride salt melts and absorbs a large amount of heat, stabilizing the reaction system temperature within the reaction temperature range, thereby effectively preventing the system from overheating.

[0046] Therefore, in Comparative Example 1, the use of NaCl as a diluent and temperature regulator resulted in a weak temperature regulation effect, leading to a high-temperature reaction (even reaching around 700°C) and the formation of a certain proportion of hexagonal zinc selenide high-temperature phase. In contrast, Example 1 used a combination of NaCl and CaCl2 as a diluent and temperature regulator, resulting in a better temperature regulation effect, with the reaction temperature remaining within a more suitable range, and the products being cubic zinc selenide.

[0047] Comparative Example 2 The difference between this comparative example and Example 1 is that in Example 1, the combination of 5.9g NaCl and 8.85g CaCl2 was replaced with 14.75g CaCl2. The remaining steps remained unchanged.

[0048] The zinc selenide obtained in this comparative example was tested and found to contain 7.4% hexagonal zinc selenide high-temperature phase, with the remainder being cubic zinc selenide.

[0049] Calcium chloride still has a relatively high melting point of 772℃ and a specific heat capacity of about 0.92 J / (g·℃), so it still cannot melt in a self-propagating reaction, and its heat absorption is also lower than that of the combination of NaCl and CaCl2.

[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that in Example 1, the acetic acid aqueous solution was replaced with deionized water, meaning that the reaction product in this comparative example was washed with deionized water. All other steps remain unchanged.

[0051] The zinc selenide product obtained in this comparative example was tested and found to contain 0.7% ZnO and 6.2% Zn, with the remainder being cubic zinc selenide. This indicates that deionized water cannot completely remove excess unreacted Zn and ZnO.

[0052] Example 2 The purity of zinc powder and selenium powder raw materials is not less than 99.95%; NaCl, KCl and CaCl2 are all reagent grade, and the content of insoluble impurities is <10ppm.

[0053] A reaction mixture consisting of 101.4 g zinc powder (1.55 mol), 116 g selenium powder (1.47 mol), 54 g NaCl, 18 g KCl, and 74 g CaCl2 (the composite inorganic salt powder composed of 54 g NaCl, 18 g KCl, and 74 g CaCl2 has an initial melting temperature of 475°C and a complete melting temperature of approximately 520°C) was placed in a zirconia crucible and mechanically vibrated for mixing. The stoichiometric ratio of Zn to Se was 1.05:1, the composite chloride salt accounted for 40.2% of the reaction mixture by weight, and the average particle size of the reaction mixture was 45 μm. The zirconia crucible containing the mixture was placed inside a reaction vessel, and a resistance wire for initiating the reaction was inserted into the mixture. The vessel was then evacuated to 10°C. -3 The pressure was lower than 0.3 MPa, and high-purity Ar gas was refilled to 0.3 MPa. A self-propagating reaction was initiated exothermically by applying a 3 A current to a tungsten resistance wire. After the reaction was complete and the container was allowed to cool naturally, the product was opened and removed. The product was immersed in a 0.1 mol / L tartaric acid aqueous solution, shaken and soaked for 30 minutes, filtered, washed three times with deionized water, and dried overnight in a vacuum oven at 60°C to obtain single-phase cubic zinc selenide with a purity of 99.99%.

[0054] Example 3 The difference between this embodiment and Embodiment 2 is that in Embodiment 2, the zinc powder was adjusted from 101.4g to 105.8g, meaning the stoichiometric ratio of Zn to Se was 1.1:1, and the composite chloride salt accounted for 39.7% of the total weight of the reactants. The remaining steps remained unchanged. This embodiment yielded single-phase cubic zinc selenide with a purity of 99.96%.

[0055] Example 4 The difference between this embodiment and Embodiment 2 is that in Embodiment 2, the composite chloride salt was replaced by a composite inorganic salt combination of 72g LiCl and 72g Li2SO4 instead of the combination of 54g NaCl, 18g KCl, and 74g CaCl2 (the composite inorganic salt powder composed of 72g LiCl and 72g Li2SO4 has an initial melting temperature of approximately 482°C and a complete melting temperature of approximately 515°C). The remaining steps remain unchanged. This embodiment yields single-phase cubic zinc selenide with a purity of 99.93%.

[0056] Example 5 The difference between this embodiment and Embodiment 2 is that in Embodiment 2, the composite chloride salt was replaced by a composite inorganic salt combination of 96g Li₂SO₄ and 48g NaCl instead of the combination of 54g NaCl, 18g KCl, and 74g CaCl₂. (The composite inorganic salt powder composed of 96g Li₂SO₄ and 48g NaCl has an initial melting temperature of 490°C and a complete melting temperature of approximately 530°C.) The remaining steps remain unchanged. This embodiment yields single-phase cubic zinc selenide with a purity of 99.95%.

[0057] As described above, the basic principles, main features, and advantages of the present invention have been shown and described. Those skilled in the art should understand that the present invention is not limited to the above embodiments, which are merely preferred embodiments and should not be construed as limiting the scope of the invention. All equivalent changes and modifications made in accordance with the scope of the patent and the description should still fall within the scope of the present invention. The scope of protection of this invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing zinc selenide, characterized in that, Includes the following steps: The reaction raw materials, consisting of zinc powder, selenium powder, and composite inorganic salt powder, are mixed evenly and then subjected to a self-propagating reaction to obtain a mixture. The composite inorganic salt powder is composed of at least two inorganic salts, and the eutectic point temperature is 475-600℃; The mixture is soaked in a weakly acidic aqueous solution to remove soluble substances, then washed with water and dried to obtain zinc selenide; The zinc selenide has a cubic phase.

2. The method for preparing zinc selenide according to claim 1, characterized in that, The stoichiometric ratio of the zinc powder and the selenium powder is 1.05-1.25:1; The purity of the zinc powder and the purity of the selenium powder are each not less than 99.95%.

3. The method for preparing zinc selenide according to claim 1, characterized in that, The composite inorganic salt powder accounts for 20-40% of the weight of the reaction raw materials; The average particle size of the reaction raw materials is 5-50 μm.

4. The method for preparing zinc selenide according to claim 1, characterized in that, The at least two inorganic salts are either water-soluble or acid-soluble at room temperature.

5. The method for preparing zinc selenide according to claim 4, characterized in that, The composite inorganic salt powder is selected from chloride salts and / or sulfate salts.

6. The method for preparing zinc selenide according to claim 5, characterized in that, The composite inorganic salt powder is selected from the following systems: NaCl-CaCl2 binary system, KCl-CaCl2 binary system, LiCl-Li2SO4 binary system, Li2SO4-NaCl binary system, NaCl-KCl-CaCl2 ternary system, Na2SO4-KCl-CaCl2 ternary system, or NaCl-KCl-BaCl2 ternary system.

7. The method for preparing zinc selenide according to claim 6, characterized in that, In the NaCl-CaCl2 binary system, the weight percentage of NaCl is 40-50 wt%, and the weight percentage of CaCl2 is 50-60 wt%. The KCl-CaCl2 binary system is composed of 40-50 wt% KCl and 50-60 wt% CaCl2 by weight (100% by weight). The Li₂SO₄-NaCl binary system, by weight, comprises 15.5-30.5-50-70 wt% Li₂SO₄ and 30-50 wt% NaCl. The Li₂SO₄-NaCl binary system, by weight, comprises 66-78 wt% Li₂SO₄ and 22-34 wt% NaCl. The NaCl-KCl-CaCl2 ternary system, by weight, comprises 30-50 wt% NaCl, 5-20 wt% KCl, and 40-60 wt% CaCl2. The Na2SO4-KCl-CaCl2 ternary system, by weight, comprises 20-33 wt% Na2SO4, 17-25 wt% KCl, and 46-58 wt% CaCl2. The NaCl-KCl-BaCl2 ternary system is based on a 100% weight ratio, with NaCl accounting for 15-35 wt%, KCl accounting for 20-40 wt%, and BaCl2 accounting for 30-50 wt%.

8. The method for preparing zinc selenide according to claim 1, characterized in that, The self-propagating reaction is initiated by the exothermic reaction of the resistance wire current, with a current intensity of 3-20A and a protective gas atmosphere. The reaction temperature range of the self-propagating reaction is 475-675℃.

9. The method for preparing zinc selenide according to claim 1, characterized in that, The concentration of the weakly acidic aqueous solution is 0.05-0.5 mol / L; The weak acid in the weakly acidic aqueous solution is selected from organic weak acids.

10. The method for preparing zinc selenide according to claim 9, characterized in that, The organic weak acid is selected from one or more of malic acid, acetic acid, tartaric acid, propionic acid, and citric acid.